ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRATEGI PEMBERIAN KREDIT DAN DAMPAKNYA TERHADAP NON-PERFORMING LOAN (Studi Kasus pada Bank Perkreditan Rakyat Provinsi Daerah Istimewa Yogyakarta) - Qori Al Banin (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
Research was conducted at the Rural Bank of Yogyakarta Province, with the title: "Analysis of Factors Affecting Lending Strategy and Its Impact on Non-Performing Loan" (Case Study on Rural Bank of Yogyakarta Province). The purpose of this study was to determine the effect of external environment, internal environment of the lending strategy as well as the influence of credit strategy against non-performing loans at the Rural Bank Province Yogyakarta. The analytical tool used is multiple regressions.From the result and data analysis can be concluded that: 1) the external environment has a significant influence on the rural bank's lending strategy, based on the calculate of multiple linear regression analysis, where the t value bigger than value of t table; 2) bank's internal environment has a significant influence on the rural bank's lending strategy, based on the calculate of multiple linear regression analysis, where the obtained t value is bigger than value t table; and 3) lending strategies have significant effects on non-performing loans at the Rural Bank in Yogyakarta Province, based on the calculate of simple linear regression analysis, where the obtained t value variable lending strategy against non-performing loans is smaller than the value of t table.